Case Report: Mucocele-Like Tumor of the Breast Associated With Ductal Carcinoma In Situ - Jiang, Ying; Chai, Li; Dong, Dandan; Chughtai, Aamer Rasheed; Kong, Weifang (Frontiers in Oncology, 2022)
Mucocele-like tumor of the breast is histologically characterized as mucin-containing cysts with mucin leaking to the stroma. It could be associated with ADH, DCIS, and IDC. We report a case of mucocele-like tumor of the breast associated with DCIS confirmed by paraffin section. We review the literature and discuss the imaging features, pathology and clinical management of the lesion. These lesions demonstrate characteristic imaging features, and we especially highlight the MR characteristics as they have not been well documented. Performing a diagnostic fine needle aspiration cytology (FNAC) of mucocele-like tumor carries a risk of tumor underestimating, therefore excision for all mucocele-like tumors is suggested to be best approach. But some recent reports recommend close follow-up for patients with low risk factors who have mucocele-like tumor without atypia on FNAC.